2006
DOI: 10.1242/jcs.02801
|View full text |Cite
|
Sign up to set email alerts
|

PTEN couples Sema3A signalling to growth cone collapse

Abstract: Distinct changes in glycogen synthase kinase-3 (GSK-3) signalling can regulate neuronal morphogenesis including the determination and maintenance of axonal identity, and are required for neurotrophin-mediated axon elongation. In addition, we have previously shown a dependency on GSK-3 activation in the semaphorin 3A (Sema3A)-mediated growth-cone-collapse response of sensory neurons. Regulation of GSK-3 activity involves the intermediate signalling lipid phosphatidylinositol 3,4,5-trisphosphate, which can be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 37 publications
(41 reference statements)
11
118
0
1
Order By: Relevance
“…In support of this concept, we observed concurrent reductions in pAkt and pGSK3␤ expression within the injury milieu where PTEN was also expressed. Decreased phosphorylation of these molecules leads to growth cone collapse and a less supportive microenvironment at the nerve trunk injury site (Eickholt et al, 2002; Jones Chadborn et al, 2006). Our data have confirmed an active role of PTEN through pharmacological and knockdown approaches in adult peripheral neurons.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In support of this concept, we observed concurrent reductions in pAkt and pGSK3␤ expression within the injury milieu where PTEN was also expressed. Decreased phosphorylation of these molecules leads to growth cone collapse and a less supportive microenvironment at the nerve trunk injury site (Eickholt et al, 2002; Jones Chadborn et al, 2006). Our data have confirmed an active role of PTEN through pharmacological and knockdown approaches in adult peripheral neurons.…”
Section: Discussionsupporting
confidence: 67%
“…Two major downstream targets of PI3-K signaling, Akt and GSK3␤, which have been shown to be influenced by PTEN (Chadborn et al, 2006), were also identified in sensory neurons and axons (Fig. 4).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Axonal growth is channeled through tissues during development without disrupting them, while invasion of tissue by cancer cells is disruptive and may result in the death of the host. The semaphorin Sema3A inhibits neurite outgrowth by inhibiting the phosphorylation of Akt (Chadborn et al, 2006). We have found that the protein kinase inhibitor staurosporine is lethal for N1E-115 cells when applied to undifferentiated cells (C.M.…”
Section: Neuroblastoma-derived Cell Linesmentioning
confidence: 99%